Adolescent Birth Rate: Between Women Participation in Parliament or Women Population with Secondary Education - Arisandi, Bobi; Suci, Perwita (Universitas Terbuka, 2024)
This study investigates the causal relationship between women’s participation in parliament and the proportion of women with secondary education on the global adolescent birth rate. Utilizing data from the United Nations Development Programme’s Gender Inequality Index, the research adopts a quantitative, explanatory design to examine how these independent variables influence adolescent birth rates across countries. Multiple linear regression analysis was employed to test the proposed hypotheses. The results reveal a divergent pattern: Women’s participation in parliament (X1) shows a positive causal relationship with the adolescent birth rate (coefficient = 0.009547). In contrast, the proportion of women with secondary education (X2) demonstrates a statistically significant negative relationship (coefficient = -0.730165). These findings indicate that contrary to expectations, increased parliamentary representation alone does not significantly contribute to reducing adolescent birth rates. In contrast, a higher percentage of women receiving secondary education is significantly associated with lower adolescent birth rates. These results underscore the urgent need to prioritize female education as a more effective strategy for addressing adolescent fertility globally. While political representation remains important for broader gender equality goals, this study contributes to the existing literature by highlighting that educational attainment among women has a more direct and measurable impact on adolescent reproductive outcomes. The findings provide valuable insights for policymakers, international development agencies, and gender equity advocates seeking data-driven approaches to reduce adolescent births and improve gender-sensitive health and education policies.